2014
DOI: 10.1016/j.biopsych.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Lower Amygdala Volume in Men is Associated with Childhood Aggression, Early Psychopathic Traits, and Future Violence

Abstract: Background Reduced amygdala volume has been implicated in the development of severe and persistent aggression and the development of psychopathic personality. Using longitudinal data, the current study examined whether males with lower amygdala volume have a history of aggression and psychopathic features dating back to childhood, and are at increased risk for engaging in future aggression/violence. Methods Participants were selected from a longitudinal study of 503 males initially recruited when they were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
151
1
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 216 publications
(167 citation statements)
references
References 49 publications
10
151
1
5
Order By: Relevance
“…Some studies have shown that neurobiological markers can predict, over and above well-replicated psychosocial risk factors, which individuals will demonstrate antisocial or psychopathic traits 101,102 . The two recent imaging studies described above 18,79 , together with multiple studies identifying psychophysiological and hormone predictors of future offending, provide some support for the conclusions made in a Royal Society report that neuroscience may have future value in predicting reoffending 103 .…”
Section: Predictionmentioning
confidence: 75%
See 2 more Smart Citations
“…Some studies have shown that neurobiological markers can predict, over and above well-replicated psychosocial risk factors, which individuals will demonstrate antisocial or psychopathic traits 101,102 . The two recent imaging studies described above 18,79 , together with multiple studies identifying psychophysiological and hormone predictors of future offending, provide some support for the conclusions made in a Royal Society report that neuroscience may have future value in predicting reoffending 103 .…”
Section: Predictionmentioning
confidence: 75%
“…One study showed that reduced functioning in the anterior cingulate during a go/no-go task in prisoners doubled the likelihood of re-arrest three years later 79 . A second study of high-risk community males showed that reduced amygdala volume at age 26 was associated with violent offending three years later 18 . As has been observed in other biological longitudinal research, both studies showed predictive utility of brain measures over and above past history of antisocial behavior and other confounds.…”
Section: Brain Imaging and Neurologymentioning
confidence: 99%
See 1 more Smart Citation
“…On one side, some research has argued that the neural deficits and behaviors of juvenile psychopaths are stable, long-term factors that lead to adult psychopathic behavior and offending (Loney et al, 2007;Pardini et al, 2014;Anderson & Kiehl, 2014). Since juvenile psychopaths share many of the same neural deficits and personality characteristics documented in adult psychopaths, as suggested by this review, many have reported that the deficits and behaviors of juvenile psychopathy should be considered a developmental antecedent to adult psychopathy (Barry et al, 2000;Lynam et al, 2005;Lynam et al, 2007;Frick, 2009).…”
Section: Predictionmentioning
confidence: 99%
“…It was found that in adolescence and young adulthood, lower amygdala volume was also associated with proactive aggression. More importantly, "this is the irst study to demonstrate that adult men with lower amygdala volume were at increased risk for exhibiting future aggression, violence, and psychopathic traits, even after controlling for earlier levels of these features and several potential confounds" [83].…”
Section: Neurobiological Factorsmentioning
confidence: 95%